ANALISIS PENDAPATAN DAN STRATEGI PEMASARAN AGROINDUSTRI TAHU PADA UD. AL-IKHLAS - Ahmad Fa’iz; Yasmini Suryaningsih (Program Studi Agribisnis Fakultas Pertanian, 2015)
The purpose of the study is to know the agroindustry revenues tofu at UD. Al –lkhlas and marketing strategy of agroindustry tofu at ud. al-ikhlas in the village of curah jeru the district of panji. Samples are taken as one that entrepreneurs processing soybeans into tofu at UD. Al-Ikhlas in the village of Curah Jeru the District of Panji Regency of Situbondo. The results showed that the revenue of the agroindustry tofu during the month carried of businessman UD Al-Ikhlas profitable, in which the agroindustry tofu business income earned over a period of a month to reach Rp. 14.920.500, -. Marketing strategies for agroindustry tofu at UD Al-Ikhlas In the village Curah Jeru District of Panji Regency of Situbondo running well. This can occur because the product tofu of the UD Al-Ikhlas has a market share and consumers are much in Situbondo and products may interest the public. Sales tofu too high so as to increase revenue and profit producer. Suggestions from researchers to entrepreneurs tofu the UD Al-Ikhlas which should increase again the number of production tofu because the company already has a lot of market share and good marketing, increased production should also be followed by the addition of labor, the expansion of marketing and distribution as well as adding a branch of production and marketing